Calm Hu ram lambs assigned by temperament classification are healthier and have better meat quality than nervous Hu ram lambs. (May 2021) - Zhang, Jinying; Qian, Shuhan; Chen, Jiahao; Ding, Luoyang; Wang, Mengzhi; Maloney, Shane K.; Blache, Dominique
Abstract: The objective of this study was to evaluate the effects of temperament classification (assessed using an arena test) on health and productivity of Hu ram lambs. In experiment one, eight ram lambs classified as calm and eight classified as nervous (selected from 100 ram lambs) were fed individually for 60-days to compare food intake, food digestibility, weight gain, and biochemical indices of health. In experiment two, nine ram lambs classified as calm and nine classified as nervous (selected from 150 ram lambs) were fed in a group and slaughter traits, meat quality, and muscle histology were compared. Calm lambs had higher dry matter digestibility, lower serum TNF-α, higher total antioxidant capacity, higher total superoxide dismutase activity, higher dressing percentage, higher cross-sectional area of loin, higher myofibre density, lower ultimate pH of the meat, and higher meat redness, than nervous lambs. Selection for calm temperament could be beneficial to health, slaughter, and carcass traits in Hu ram lambs.